Australian general practitioners' perspectives on integrating specialist diabetes care with primary care: qualitative study - Rachael Taylor; Shamasunder Acharya; Martha Parsons; Ushank Ranasinghe; Kerry Fleming; Melissa L. Harris; Deniz Kuzulugil; Julie Byles; Annalise Philcox; Meredith Tavener; John Attia; Johanna Kuehn; et al. (BMC, 2023)
Abstract Background Improving the coordination and integration of health services is recognised nationally and internationally as a key strategy for improving the quality of diabetes care. The Australian Diabetes Alliance Program (DAP) is an integrated care model implemented in the Hunter New England Local Health District (HNELHD), New South Wales (NSW), in which endocrinologists and diabetes educators collaborate with primary care teams via case-conferencing, practice performance review, and education sessions. The objective of this study was to report on general practitioners' (GPs) perspectives on DAP and whether the program impacts on their skills, knowledge, and approach in delivering care to adult patients with type 2 diabetes. Methods Four primary care practices with high rates of monitoring haemoglobin A1c (HbA1c) levels (> 90% of patients annually) and five practices with low rates of monitoring HbA1c levels (< 80% of patients annually) from HNELHD, NSW provided the sampling frame. A total of nine GPs were interviewed. The transcripts from the interviews were reviewed and analysed to identify emergent patterns and themes. Results Overall, GPs were supportive of DAP. They considered that DAP resulted in significant changes in their knowledge, skills, and approach and improved the quality of diabetes care. Taking a more holistic approach to care, including assessing patients with diabetes for co-morbidities and risk factors that may impact on their future health was also noted. DAP was noted to increase the confidence levels of GPs, which enabled active involvement in the provision of diabetes care rather than referring patients for tertiary specialist care. However, some indicated the program could be time consuming and greater flexibility was needed. Conclusions GPs reported DAP to benefit their knowledge, skills and approach for managing diabetes. Future research will need to investigate how to improve the intensity and flexibility of the program based on the workload of GPs to ensure long-term acceptability of the program.